Patient-derived orthotopic xenograft models of sarcoma. (28th January 2020) - Igarashi, Kentaro; Kawaguchi, Kei; Murakami, Takashi; Miyake, Kentaro; Kiyuna, Tasuku; Miyake, Masuyo; Hiroshima, Yukihiko; Higuchi, Takashi; Oshiro, Hiromichi; Nelson, Scott D.; Dry, Sarah M.; Li, Yunfeng; et al.
Abstract: Sarcoma is a rare and recalcitrant malignancy. Although immune and novel targeted therapies have been tested on many cancer types, few sarcoma patients have had durable responses with such therapy. Doxorubicin and cisplatinum are still first-line chemotherapy after four decades. Our laboratory has established the patient-derived orthotopic xenograft (PDOX) model using surgical orthotopic implantation (SOI). Many promising results have been obtained using the sarcoma PDOX model for identifying effective approved drugs and experimental therapeutics, as well as combinations of them for individual patients. In this review, we present our laboratory's experience with PDOX models of sarcoma, and the ability of the PDOX models to identify effective approved agents, as well as experimental therapeutics. Highlights: Sarcoma is a rare and recalcitrant malignancy. Present PDOX models of sarcoma. PDOX models of sarcoma behave quite similar to patient sarcoma. PDOX models provide sarcoma patients with improved and personalized treatment options.